Porcelain Product Quality Analysis in PT XYZ - Chie, Ho Hwi; Nasution, Januar; Ayu, Ketut Gita; Septivani, Nike; Renaldi, Yualfin (Bina Nusantara University, 2015)
PT. XYZ is a company engaged in manufacturing porcelain dinner ware such as plates, cups, teapot, bowl, etc Porcelain product is safe for use and product defect will only affect the aesthetic not the functional side. The company always maintain the quality of the products produced as by maintaining a good product, in terms of visuals, will keep customers interested in the product. Good quality products characterized by quality A / B and C, and the product defect characterized by the quality of D, Lost, and BU. Concepts and methods used to analyze is a statistical process control (SPC) which includes Pareto diagram, fraction nonconformities, flow charts and fishbone diagrams and management tools (fault tree analysis). Statistical Process Control (SPC) is one of the methods, which includes Pareto charts, fraction nonconformities, flow chart, and fishbone diagram and also management tools (fault tree analysis). SPC is useful to find the facts from the problems and factors that affect the quality of the products, while fault tree analysis is useful to analyze each of the production process.